Effects of an 8-week multimodal program on thoracic posture, glenohumeral range of motion and serve performance in competitive young tennis players - Le Solliec, Tom; Blache, Yoann; Rogowski, Isabelle (Frontiers in Sports and Active Living, 2023)
Introduction Intensive tennis practice is known to generate sport-specific adaptations at the shoulder region and influence the sagittal spinal curvature. However, increased thoracic kyphosis decreases the shoulder functional capacity, which could limit tennis performance. Therefore, the aim of this study was to investigate the effects of an 8-week multimodal program on thoracic posture, glenohumeral range of motion, and serve performance in competitive young tennis players. Methods Eighteen male and four female players (age: 16.0 ± 2.4 years, height: 170.7 ± 11.0 cm; mass: 62.1 ± 11.5 kg; International Tennis Number: 3–4) performed their regular training during 8 weeks, which was used as a reference period, and implemented a multimodal program including stretching, strengthening, and myofascial release exercises, four times per week during 8 additional weeks, which corresponded to the intervention period. The thoracic curvature angle and mobility, the biacromial and interscapular distances, the glenohumeral range of motion and the tennis serve performance were assessed three times, i.e., before and after the regular training and after the 8-week multimodal program. Results The results showed that the 8-week regular training had no significant effects on thoracic curvature angle [effect size (ES) = 0.02–0.36, p = 0.06–0.46] and mobility (ES = 0.05–0.26, p = 0.13–0.42), biacromial (ES = 0.05, p = 0.18) and interscapular distances (ES = 0.03, p = 0.45), ranges of motion in glenohumeral internal (ES = 0.04, p = 0.43) and external rotation (ES = 0.43, p = 0.06), and tennis serve accuracy (ES = 0.33, p = 0.07) and velocity (ES = 0.09, p = 0.35). The 8-week multimodal program increased moderately the thoracic mobility (ES = 0.55, p = 0.01), moderately to strongly the serve accuracy and velocity (ES = 0.65, p = 0.003, for both), strongly decreased the interscapular distance (ES = 1.02, p < 0.001), and strongly increased the range of motion in glenohumeral internal (ES = 0.90, p < 0.001) and external rotation (ES = 1.49, p < 0.001). Discussion These findings indicated that an 8-week multimodal program, including spine and glenohumeral mobility and shoulder girdle strength exercises, performed four times per week during 8 weeks, is moderately relevant to rectify the sagittal thoracic curvature in competitive tennis players, while such a program may help regain the range of motion in glenohumeral rotation without tennis serve performance impairment.